The Effect of Playing Card Technique to Improve Students™ Speaking Skill the Seventh Grade Students of SMP Swasta Prayatna Medan - Albalqis, Nabila; Prawiyata, Yugi Diraga (Universitas Negeri Medan, 2023)
The object of this research is to discuss students' speaking skills using playing card techniques. This research was conducted at SMP Swasta Prayatna Medan. The research consists of two classes. In the sample, the researcher chose class VII-1 consisting of 20 students as the experimental group and class VII-2 consisting of 20 students as the control group. The total is 40 students. During this research, researchers have discovered the importance of which effect in an experimental class using the playing card technique. Students get good grades, but in the control class students get low grades. In this study, the results obtained were that the average of the experimental group was better than the average of the control group. Mx = 16 while My = 12 where t (impact) = 1.801. After the data was analyzed it turned out that the alternative hypothesis or Ha was accepted. From these data it can be concluded that there is an influence on the importance of students' speaking skills by using the playing card technique. In the teaching process, especially on students' speaking abilities.